A Bifactor Model of Personality Organization. Issue 2 (4th March 2021) - Hörz-Sagstetter, Susanne; Volkert, Jana; Rentrop, Michael; Benecke, Cord; Gremaud-Heitz, Daniela J.; Unterrainer, Human-Friedrich; Schauenburg, Henning; Seidler, Daniel; Buchheim, Anna; Doering, Stephan; Feil, Markus G.; Clarkin, John F.; et al.
Abstract: The aim of this study was to explore the viability of a bifactor model for the Inventory of Personality Organization (IPO), which is a self-report measure of personality functioning based on Kernberg's model of personality organization. A heterogeneous, predominantly clinical sample ( N = 616) completed the German 83-item version of the IPO. Confirmatory and Exploratory Factor Analyses were applied to explore the factor structure of the IPO. We were able to establish a bifactor model with a general factor of personality functioning and three specific factors (Aggression, Reality Testing, Moral Values), which represent additional dimensions of personality organization. Virtually all items showed substantial positive loadings on the general factor, explaining roughly 66% of the common variance. Furthermore, we found support for convergent and discriminant validity of general and specific factors with regard to interview-based assessments of personality disorders and personality organization. The results lend support to a bifactor approach to Kernberg's model of personality organization. We also present a 30-item brief form of the IPO that efficiently implements the bifactor approach and may be further validated in future studies.